Decreased antimony uptake and overexpression of genes of thiol metabolism are associated with drug resistance in a canine isolate of Leishmania infantum. Issue 2 (August 2016) - Gómez Pérez, Verónica; García-Hernandez, Raquel; Corpas-López, Victoriano; Tomás, Ana M.; Martín-Sanchez, Joaquina; Castanys, Santiago; Gamarro, Francisco
Abstract: Visceral leishmaniasis (VL) caused by the protozoan parasite Leishmania infantum, is one of the most important zoonotic diseases affecting dogs and humans in the Mediterranean area. The presence of infected dogs as the main reservoir host of L . infantum is regarded as the most significant risk for potential human infection. We have studied the susceptibility profile to antimony and other anti-leishmania drugs (amphotericin B, miltefosine, paromomycin) in Leishmania infantum isolates extracted from a dog before and after two therapeutic interventions with meglumine antimoniate (subcutaneous Glucantime ®, 100 mg/kg/day for 28 days). After the therapeutic intervention, these parasites were significantly less susceptible to antimony than pretreatment isolate, presenting a resistance index of 6-fold to Sb III for promastigotes and >3-fold to Sb III and 3-fold to Sb V for intracellular amastigotes. The susceptibility profile of this resistant L . infantum line is related to a decreased antimony uptake due to lower aquaglyceroporin-1 expression levels. Additionally, other mechanisms including an increase in thiols and overexpression of enzymes involved in thiol metabolism, such as ornithine decarboxylase, trypanothione reductase, mitochondrial tryparedoxin and mitochondrial tryparedoxin peroxidase, could contribute to the resistance as antimony detoxification mechanisms. A major contribution of this study in a canine L . infantum isolate is to find an antimony-resistant mechanism similar to that previously described in other human clinical isolates. Graphical abstract: Highlights: Antimony resistance in a Leishmania infantum line from a dog is reported. Resistance due to decrease antimony uptake by lower aquaglyceroporin-1 expression. An increase in thiols metabolism contribute to antimony resistance.